The empirical determinants of credit default swap spreads: a quantile regression approach - Pires, P.; Pereira, J.; Martins, L. F. (European Financial Management, 2015)
We study the empirical determinants of Credit Default Swap (CDS) spreads through quantile regressions. In addition to traditional variables, such as implied volatility, put skew, historical stock return, leverage, profitability, and ratings, the results indicate that CDS premiums are strongly determined by CDS illiquidity costs, measured by absolute bid-ask spreads. The quantile regression approach reveals that high-risk firms are more sensitive to changes in the explanatory variables that low-risk firms. Furthermore, the goodness-of-fit of the model increases with CDS premiums, which is consistent with the credit spread puzzle.